2018
DOI: 10.1111/jora.12340
|View full text |Cite
|
Sign up to set email alerts
|

Do Hostile School Environments Promote Social Deviance by Shaping Neural Responses to Social Exclusion?

Abstract: The present study examined adolescents' neural responses to social exclusion as a mediator of past exposure to a hostile school environment (HSE) and later social deviance, and whether family connectedness buffered these associations. Participants (166 Mexican-origin adolescents, 54.4% female) reported on their HSE exposure and family connectedness across Grades 9-11. Six months later, neural responses to social exclusion were measured. Finally, social deviance was self-reported in Grades 9 and 12. The HSE-soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 92 publications
0
27
0
Order By: Relevance
“…Although not primary regions of interest, we also found that older participants recruited several other regions during successful inhibition toward appetitive contexts in the presence of their mother, including the dACC, fusiform, and temporal pole. The dACC is associated with social stress (Schriber et al, 2018), suggesting that the monitoring of a caregiver may induce social motivation to improve performance during adolescence. The fusiform gyrus has been proposed to detect salient social information (Nelson, Leibenluft, McClure, & Pine, 2005) and is implicated during adolescent decisionmaking in the presence of mothers and peers (Guassi Moreira & Telzer, 2018;van Hoorn, McCormick, Rogers, Ivory, & Telzer, 2018).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Although not primary regions of interest, we also found that older participants recruited several other regions during successful inhibition toward appetitive contexts in the presence of their mother, including the dACC, fusiform, and temporal pole. The dACC is associated with social stress (Schriber et al, 2018), suggesting that the monitoring of a caregiver may induce social motivation to improve performance during adolescence. The fusiform gyrus has been proposed to detect salient social information (Nelson, Leibenluft, McClure, & Pine, 2005) and is implicated during adolescent decisionmaking in the presence of mothers and peers (Guassi Moreira & Telzer, 2018;van Hoorn, McCormick, Rogers, Ivory, & Telzer, 2018).…”
Section: Figurementioning
confidence: 99%
“…Social buffering is the process by which the presence of sensitive parental figures buffers youth from emotional dysregulation (Gee et al., ). Effective social buffering occurs via modulated neurobiological processes (Gunnar, Hostinar, Sanchez, Tottenham, & Sullivan, ; Hostinar & Gunnar, ; Schriber & Guyer, ), such that parental presence buffers youth from behavioral disinhibition by promoting neural regulation via the mPFC (e.g., Gee et al., ; Schriber et al., ). For example, the physical presence of mothers redirects adolescent risk‐taking behavior toward safer decision‐making (Telzer, Ichien, & Qu, 2015a), which occurs via striatum–mPFC coupling (Guassi Moreira & Telzer, ).…”
mentioning
confidence: 99%
“…Schriber et al. () examined social influences of both parents and peers in their longitudinal study. They examined neural responses to social exclusion in hostile school environments and whether family connectedness buffered the effects of social exclusion on later deviance.…”
Section: Key Themes Explored In This Special Sectionmentioning
confidence: 99%
“…Schriber et al. () present findings on how the link between a hostile school environment and later behavioral problems may be associated with neural reactivity to social rejection. But even this association can depend upon the family environment, offering a rare developmental neuroscience study that examines the interaction between two social environments.…”
Section: The Interaction Between Brain Development and The Social Envmentioning
confidence: 99%
“…The articles in this special section nicely exemplify the strengths of applying neuroscience to psychopathology, as adolescence is a period at which many of these problems manifest themselves. All of the articles focus on patterns of functional activation associated with potential emotional and behavioral difficulties, including externalizing and conduct disorder behaviors (Brieant et al, 2018;Saxbe et al, 2018;Schriber et al, 2018;Trucco, Cope, Burmeister, Zucker, & Heitzeg, 2018), risky decision making (Hansen, Thayer, Feldstein-Ewing, Sabbineni, & Bryan, 2018;Rodrigo, Padr on, de Vega, & Ferstl, 2018), stress responsivity (T.-H. Lee, Qu, & Telzer, 2018), and depression symptomatology (K. H. Lee, Oppenheimer, et al, 2018). Recent calls have been made to build upon these insights and expand the field's scope to understanding normative processes, puberty, and the unique opportunities for positive development afforded by brain development during adolescence (Crone & Dahl, 2012;Pfeifer & Blakemore, 2012).…”
Section: An Integrative Approach That Incorporates Both Typical and Amentioning
confidence: 99%